Impact of plate Osteosynthesis on Functional Outcome in displaced midshaft Clavicular Fractures: a prospective observational study - Kumar Gohiya, Ashish; Singh Bhasin, Sushan; Sharma, Pulak; Gaur, Sanjiv (International Journal of Medical Research and Review, 2015)
Introduction: Fractures of the clavicle are common, accounting for 2.6-4% of adult fractures and 35% of injuries to the shoulder girdle. Fractures of the shaft account for 69-82% of all fractures. Prevalence of non-union or mal-union in displaced midshaft clavicular fractures after conservative treatment is higher than previously presumed. Plate fixation can help obtain firm anatomical reduction in severe displaced or comminuted fracture. We have taken up this study to evaluate the functional outcome after plate osteosynthesis ofclavicular fractures. Materials and Methods: This is a prospective study done in Department of Orthopedics at tertiary care teaching hospital in central India over period of 1 year. The patients who presented with fracture clavicle and fulfilled the inclusion criteria were studied. Functional outcome was evaluated using modified Constant and Murley scoring system. Results: 24 patients of displaced midshaft clavicle fracture matching inclusion criteria were included in this study. Follow up evaluation of the patients was done at the desired interval with a minimal follow up of 6 months. 52.17% were in the age group of 20-29 years. 73.91% of patients studied were males. Type-2 middle third fracture type-2 B1 was encountered in 78.26 % of patients. The mean modified Constant Shoulder Score was 65.39 with range 48-72. In this study 17 patients (73.91 %) had very good functional outcome. Conclusion: Use of locking plates for displaced midshaft clavicle fractures results in early union with very good functional outcome and is associated with very low complication rates.